Optimization of African indigenous vegetables production in sub Saharan Africa: a review - Jefline J. Kodzwa; Godwil Madamombe; Esther N. Masvaya; Justice Nyamangara (CABI Agriculture and Bioscience)
Abstract The numerous types of African Indigenous Vegetables (AIVs) in sub-Saharan Africa are not extensively cultivated, even after the realization of their superior nutritional, health benefits, and higher resistance to climate change. The recent increase in demand for AIVs brings about the need to match cultivation with consumption to prevent the extinction of these nutritious vegetables through overexploitation. This review aims to assess the most common AIVs and the associated agronomic practices in their production by smallholder farmers in Zimbabwe and SSA in general for potential commercialization. Amaranthus, Cleome gynandra, Bidens pilosa, Abelmoschus esculentus, Vigna unguiculata, Cucurbita spp. and Corchorus molitorius are some of the most consumed AIVs in sub-Saharan Africa. Plant density should balance between leaf quality and leaf and seed yield per unit area. Transplanting and sowing AIVs in lines as pure stand can optimize production when compared to broadcasting. Nutrient application whether organic or inorganic is crucial together with harvesting leaves in 1 to 2 weeks interval and removing flowers to increase budding for optimized AIVs production. There is vast information on the indigenous vegetables found and preferred in SSA but scarce information on their performance under different plant nutrition management regimes and different agroecological regions. Research is required to increase production and to improve the nutrient content of AIVs.